MD-102 Endpoint Administrator - Bryan, Wes; Deal, Lauren (Packt Publishing Ltd., 2024)
This course is designed to equip IT professionals with the knowledge and skills to efficiently deploy, manage, and secure Windows clients and devices using Microsoft Intune and Entra ID. Starting with an overview of the course and the latest updates, learners will delve into selecting and customizing Windows client editions, creating deployment tools, and implementing Autopilot for seamless device registration and deployment. As the course progresses, participants will gain expertise in managing identities and compliance policies using Intune. They will learn to implement and manage compliance policies, monitor device compliance, and handle user authentication and group management in Windows environments. The integration of Microsoft Entra ID for device registration and the use of Active Directory connectors further enhances the management capabilities covered in this course. In the final sections, the focus shifts to advanced device management, maintenance, and security. Learners will explore configuring enrollment, deploying security baselines, and using Microsoft Defender for endpoint security. By the end of this course, participants will have a comprehensive understanding of using Microsoft Intune and Entra ID to manage and secure their organization's IT infrastructure.
Online resource; title from title details screen (O'Reilly, viewed June 3, 2024)
Keywords: Microsoft Windows (Computer file) -- Study guides -- Examination; Microcomputers -- Study guides -- Maintenance and repair -- Examinations; Electronic data processing personnel -- Certification; Micro-ordinateurs; Entretien et réparations; Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet